Evaluation and modeling of the variation of electromagnetic field on the cross section of a transmission line using finite difference method (2015)
This paper present a purpose to characterize power lines in order to identify level of operation since the power grid planning. In order to model a power line was required the use of computational tools to generate a mathematical model in MATLAB, which was based on the finite difference method and represent the electromagnetic field (EMF) contribution. The results were contrasted with real and measured values taken from a cross section of a power line that was previously modeled. Statistical analysis showed an accurate estimation of the electric and magnetic field emitted by the line identifying the same shape of the plotted curve and values in an acceptable range.